Fuzzy logic and applications : 12th International Workshop, WILF 2018, Genoa, Italy, September 6-7, 2018, Revised selected papers /: 12th International Workshop, WILF 2018, Genoa, Italy, September 6-7, 2018, Revised selected papers. (2019) - Unknown
No abstract available